A new Malaxis (Orchidaceae: Malaxidinae) from the Campos de Altitude of the Atlantic rainforest in southern Brazil - Faria dos Santos, Thiago [UNESP]; de Camargo Smidt, Eric (Wiley, 2023)
Malaxis ybytus is proposed as a new species from the wetlands of the Campos de Altitude of the Atlantic rainforest of south Brazil, Serra do Araçatuba\Papanduva mountain chain. It is described, illustrated, and compared with other similar species. The new species is similar to Malaxis cipoensis and Malaxis sertulifera, but it is recognised by its flat to slightly conduplicate leaves, densely congested inflorescence with small flowers bearing free lateral sepals and four foveas in the lip. Due to the high degree of endemism in this environment, the few collection records and the anthropic pressure in the region, we infer that the species is critically endangered (CR) based in criterium D of the IUCN.
Keywords: endangered; high-altitude fields; monocots; orchids